Interactions of the scientific results and practice in the biodiesel plant in Mátészalka, in the eastern tri-border area of Hungary - Góczi, István (Acta Agraria Debreceniensis, 2009)
This study summarises the observations about the operation of the first Hungarian model-like biodiesel plant (which has a producer background). In order to efficiently and safely operate the applied technology and to produce biodiesel that conforms to international standards, it was indispensable to apply the scientific results in practice and to develop a cooperation with the University of Debrecen (Centre of Agricultural Sciences and Engineering). The biodiesel plant has a significant importance from the aspects of the Eastern tri-border area and the North Great Plain region.